Comprehensive treatment approaches for skeletal deformities in hypophosphatasia: a case study of ALPL gene variants - Jiao, Qiongjie; Ma, Guixia; Ni, Qian (Frontiers in Pediatrics, 2025)
This study presents a case report of an 11-year-old boy with hypophosphatasia due to compound heterozygous ALPL gene genetic variants, focusing on the treatment effects of comprehensive approaches for this rare genetic disorder. The patient's diagnosis was established based on respiratory distress and cough, accompanied by anterior chest wall protrusion and flattened thorax upon physical examination. Laboratory findings showed blood and cardiac abnormalities, and genetic testing identified pathogenic ALPL variants. The treatment included corrective surgery for chest wall deformities and thoracic reshaping, which led to a gradual normalization of biochemical markers postoperatively, including creatinine, calcium, magnesium, and phosphate levels, with sustained low alkaline phosphatase levels. Following surgery, respiratory function improved, as evidenced by a follow-up chest CT scan showing recovery of chest structure and resolution of lung abnormalities one-month post-discharge. This case highlights the significant enhancement in chest structure and respiratory function in patients with hypophosphatasia with ALPL gene genetic variants through comprehensive treatment strategies, emphasizing the pivotal role of genetic testing in diagnosis and the benefits of interdisciplinary collaboration in long-term patient care and quality of life enhancement.